Karakteristik Fisik dan Organoleptik Produk Mocatilla Chips dari Tepung Mocaf dan Jagung - Asmoro, Novian Wely; Hartati, Sri; Handayani, Catur Budi (Program Studi Teknologi Pangan, 2017)
The aim of this study was to determined the effect of mocaf flour and maize to the mocatilla chips physical properties and organoleptic properties. The study design using RAL method with one parameter added mocafflour as much as 0% as control, 15%, 30%, 45% and 60% (w / w). Each treatment using 3 experimental replicated unit. Analysis of texture products include mechanical testing, moisture content test and organoleptic test. Added mocaf flour ranging from 15% to 60% in the mocatilla chips no significant effect on water content but caused changes in texture becomes harder to value% deformation increased from 20.39% to 30.53%. Organoleptic characteristics on mocatilla chips has changed in color, taste, aroma and texture after adding mocaf flour compared with control, and overall the highest score of 4.6 panelists acceptance found on the product mocatilla chips with the addition of as much as 15%, so the addition of mocaf flour 15% can be used for the production mocatilla chips. it is not different physical characteristics and organoleptic with control (0% mocaf).